Effects of Xylooligosaccharides on Lipid Metabolism, Inflammation, and Gut Microbiota in C57BL/6J Mice Fed a High-Fat Diet - Li, Fang; Li, Qian; Zhang, Yu; Zhou, Xianrong; Yi, Ruokun; Zhao, Xin (Frontiers in Pharmacology, 2021)
Xylooligosaccharide (XOS) is a source of prebiotics with multiple biological activities. The present study aimed to investigate the effects of XOS on mice fed a high-fat diet. Mice were fed either a normal diet or a high-fat diet supplemented without or with XOS (250 and 500 mg/kg), respectively, for 12 weeks. The results showed that the XOS inhibited mouse weight gain, decreased the epididymal adipose index, and improved the blood lipid levels, including triglyceride (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C) levels. Moreover, XOS reduced the activity of alanine aminotransferase (ALT) and aspartate aminotransferase (AST), and alleviated the damage to the liver caused by the high-fat diet. XOS also reduced hyperlipidemia-associated inflammatory responses. Additionally, quantitative real-time polymerase chain reaction results showed that XOS intervention activated the AMP-activated protein kinase (AMPK) pathway to regulate the fat synthesis, decomposition, and β oxidation; upregulated the mRNA expression levels of carnitine palmitoyl transferase 1 (CPT-1), peroxisome proliferator–activated receptors α (PPAR-α), and cholesterol 7-alpha hydroxylase (CYP7A1); and downregulated the mRNA expression levels of acetyl-CoA carboxylase (ACC), CCAAT/enhancer-binding protein alpha (C/EBPα), and lipoprotein lipase (LPL). On the other hand, XOS enhanced the mRNA expression levels of zonula occludens-1 (ZO-1), occludin, and claudin-1 in the small intestine; increased the strength of the intestinal barrier; and optimized the composition of the intestinal microbiota. Therefore, it was concluded that XOS regulated the intestinal barrier, changed the intestinal microecology, and played an important role in preventing hyperlipidemia through the unique anatomical advantages of the gut–liver axis.